(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Relevance. Frequently ill children have been one of the leading places in the pathology of the Danish age in recent years. They make up a large percentage of those suffering from respiratory diseases, as they account for up to all registered diseases. Frequent morbidity has an adverse effect on physical development and causes significant changes in the health of children. Such children do not attend preschool institutions for a long time, which creates a difficult problem for their parents and teachers in their education and upbringing (S.M. Havelov , 1986). In addition, frequent morbidity has an important social aspect, as it causes large economic losses: payments for sick leave for caring for frequently ill children amount to. A number of studies concern the issues of medical examination and rehabilitation of frequently ill children, many of them offer seemingly effective measures to prevent frequent respiratory diseases, however, for a number of years, only a tendency to decrease the incidence has been observed. In the literature, there are isolated studies that allow actively and purposefully influencing non-immunological changes with the help of such immunocorrective drugs as levamisole, sodium nucleknate , thymalin, T-activin, vilosen . However, with their use, a number of questions arise concerning the appropriateness of their appointment, prevention of complications from their use, methods for assessing their effectiveness.